Edukasi Manfaat Pijat Oksitosin pada Ibu Post Partum di RSU Balikpapan Baru - Tri Lestari, Puji; Isfaizah; Ratna Ningrum, Riana; Banne Ringgi, Rina (Universitas Ngudi Waluyo, 2023)
Failure to express breast milk smoothly is one of the important factors in the failure of exclusive breastfeeding. Oxytocin massage is one solution to overcome irregularities in breast milk production, reduce engorgement and reduce breast milk blockages. Oxytocin can calm the mother, so that breast milk automatically comes out smoothly. Midwives, husbands or family members are people who can help mothers in providing oxytocin massage therapy. The aim of this community service is to provide knowledge and skills to postpartum mothers regarding oxytocin massage. The service activities were carried out using lecture methods and demonstrations of oxytocin massage in the postpartum education room. The activity was carried out on 3 December 2023 at RSU Balikpapan Baru for 11 postpartum mothers. After being given counseling, significant results were seen for post partum mothers in the breastfeeding process, namely increased knowledge and understanding of post partum mothers and their families about breast milk problems and solutions. Insufficient breast milk production does not only depend on nutritional problems but there are also other factors that influence it, such as psychology. and maternal environment. Then mothers and families know the benefits of oxytocin massage and can practice it. Community service is able to increase the knowledge and skills of mothers and family members about breastfeeding, how to increase breast milk production and the practice of oxytocin massage. Hopefully similar activities will continue to be held in the future. Abstrak Ketidaklancaran pengeluaran ASI menjadi salah satu factor penting dalam kegagalan pemberian ASI Eksklusif. Pijat oksitosin merupakan salah satu solusi untuk mengatasi ketidaklancaran produksi ASI, mengurangi engorgement dan mengurangi sumbatan ASI. Oksitosin yang dapat menenangkan ibu, sehingga ASI pun otomatis keluar lancar. Bidan, suami atau anggota keluarga adalah orang yang dapat membantu ibu dalam memberikan terapi pijat oksitosin. Tujuan pengabdian kepada Masyarakat ini adalah memberikan pengetahuan dan ketrampilan kepada ibu nifas tentang pijat oksitosin. Kegiatan pengadian dilakukan dengan metode ceramah dan demontrasi pijat oksitosin di ruang Learning Center RSU Balikpapan Baru. Kegiatan dilakukan pada tanggal 3 Desember 2023 di RSU Balikpapan Baru pada 11 ibu nifas. Setelah diberikan penyuluhan terlihat hasil yang bermakna terhadap ibu post partum dalam proses menyusui yaitu meningkatnya pengetahuan dan pemahaman seorang ibu post partum dan keluarga tentang masalah ASI dan solusinya, produksi ASI yang kurang tidak hanya tergantung pada masalah nutrisi tetapi juga ada faktor lain yang mempengaruhinya seperti psikis dan lingkungan ibu. Kemudian ibu dan keluarga mengetahui manfaat pijat oksitosin dan bisa mempraktekkannya. Pengabdian kepada masyarakat mampu meningkatkan pengetahuan dan keterampilan pada ibu, anggota keluarga tentang ASI, cara meningkatkan produksi ASI dan praktek pijat oksitosin. Semoga kedepan kegiatan serupa dalam terus diadakan.